GDI+ custom controls with Visual C♯ 2005 : a fast-paced example-driven tutorial to building custom controls using Visual C♯ 2005 Express Edition /: a fast-paced example-driven tutorial to building custom controls using Visual C♯ 2005 Express Edition. (2006) - Unknown
No abstract available